Flexibility of Work in the Public and Private Sector in Slovenia - Tatjana Kozjek (Central European Public Administration Review)
Discussions about flexibility of organizations in the field of work are more frequent in the recent years, mostly as a result of the economic recession. Structural changes and globalization have had a severe effect on both, organizations and employees. Therefore, organizations must remain flexible to respond to unexpected changes to the area of demand, as well as adjust to new technologies and other influences. Organizations implement various measures to increase their flexibility of work and timing of work and internal mobility of employees or in the field of wages and labor costs. The article presents results of the research which examined whether there are differences in the flexibility of organizations in the field of work between employees in the public and private sectors in Slovenia. The results showed that private organizations enabled internal, numerical, functional and locational flexibility more often than public organizations. The most flexible among public organizations are public agencies and institutions.